Effects of illness and hip fracture perceptions on coping strategies of elderly rehabilitation clients - Tone Brejc (Psihološka Obzorja, 2006)
The objective of this pilot study was to evaluate, using Leventhal's self-regulatory model of illness perceptions, the effects of subjective representations of health and hip fracture on coping strategies in a sample of 52 clients more than 65 years old at the beginning of intensive hospital rehabilitation programme. The results revealed that rehabilitation clients suffering from hip fracture preserved their sense of good general and mental health. Negative representation of hip fracture was related only to perception of temporary decline in physical activity and not to perception of other personal, social and economic consequences neither to perception of their controllability. Perception of poor physical competence influenced the use of less preferred coping strategies of behavioural, mental and alcohol/drug based disengagement, and denial. Rehabilitation clients preferred those cognitive-behavioural and emotional strategies which confirmed their perception of self-efficiency and confidence in therapeutic assistance.Strategies were thus selected according to active and planned endeavour to cope, and were based on acceptance, turning to religion, focusing and venting emotions, and seeking instrumental and social support. The study confirmed the hypothesis that negative representation of hip fracture and poor sense of physical competence had a restraining effect on the use of coping strategies. There was no evidence that coping strategies of hip fracture in elderly rehabilitation clients created a specific pattern, depending on the perception of its consequences and the appraisal of possibility to regain health control. The validity of the findings is limited by a relatively small and selected sample of cognitive intact and motivated older rehabilitation clients, use of specific, non-standardised instruments, and a cross-sectional approach.